1980
DOI: 10.1139/g80-043
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing Rates in Barley Populations in the Canadian Prairies

Abstract: Using three morphological markers, the magnitude of natural cross-fertilization in three successive generations, F,, P;, and F, of foul single crosses of barley (Hordeum vulgare L.) was estimated under dryland conditions of the Canadian Prairies. The average frequency of outcrossing was very low (0.35%). Somewhat higher rates of outcrossing were observed in a highly variable composite cross population of barley (CC XXI). CC XXI showed an overall outcrossing rate of 0.8096, when propagated under irrigated condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In addition, under cool and moist conditions, higher outcrossing rates may be caused by extended pollen viability (Hammer 1977;Lansac et al 1994;Gupta et al 2000). Our results agree with the findings of Giles et al (1974), Brown et al (1978) and Chaudhary et al (1980) who showed that cool and moist conditions promote outcrossing in barley.…”
Section: Influence Of Climatic Conditionssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, under cool and moist conditions, higher outcrossing rates may be caused by extended pollen viability (Hammer 1977;Lansac et al 1994;Gupta et al 2000). Our results agree with the findings of Giles et al (1974), Brown et al (1978) and Chaudhary et al (1980) who showed that cool and moist conditions promote outcrossing in barley.…”
Section: Influence Of Climatic Conditionssupporting
confidence: 93%
“…In any case, the discrepancy between the t m and t e estimates indicates considerable annual fluctuations of the outcrossing rate. Similar observations have been reported for barley populations under dry conditions in the Canadian Prairies (Chaudhary 1980) as well as in other self-fertilized species such as Phaseolus lunatus (Allard and Workman 1963), Avena fatua (Imam and Allard 1965) and in allogamous but self-fertile rye materials (Geiger and Schnell 1970).…”
Section: Influence Of Climatic Conditionssupporting
confidence: 81%
See 2 more Smart Citations
“…spontaneum K. Koch in the Near East. Therefore, barley is considered as a self‐pollinator with a high degree of cleistogamy (Giles et al, 1974; Brown et al, 1978; Chaudhary et al, 1980; Doll, 1987; Parzies et al, 2000). Yet, variation has been observed for spikelet opening and anther extrusion at anthesis (Virmani and Athwal, 1973; Ceccarelli, 1978; Doll, 1987; Hammer, 1984; Gupta et al, 2000; Abdel‐Ghani et al, 2003).…”
mentioning
confidence: 99%